A 'Cut-Down-To-Stop' intervention for smokers who find it hard to quit: a qualitative evaluation - J. Robinson; A. McEwen; R. Heah; S. Papadakis (BMC, 2019)
Abstract Background English Stop Smoking Services primarily deliver behavioural interventions to support abrupt quit attempts. Recent evidence suggests an alternative approach could be offered to clients involving a more gradual reduction of cigarettes smoked leading to complete abstinence, known as 'Cut Down To Stop' (CDTS). The purpose of this study was to explore the experiences of stop smoking practitioners and service users who participated in a pilot study of a CDTS service. Methods The CDTS intervention was pilot tested in a Stop Smoking Service in London, England. As part of the CDTS intervention clients who were still smoking 2 weeks after their quit date were offered tailored advice, medication and support to reduce their current smoking by half, with the aim to stop smoking altogether within a six-month period. A qualitative evaluation was conducted involving a focus group discussion with nine practitioners involved in the delivery of the CDTS intervention and telephone interviews with 18 CDTS service users. Thematic analysis was performed. Results Service users and practitioners were very positive about their experience with the CDTS intervention. The intervention was found to be an effective way of keeping clients engaged with the service and was felt to increase the likelihood they might quit and/or re-engage in service for future quit attempts. Elements that contributed to the attractiveness of the CDTS intervention included: 1) the trust and empathetic relationship developed between service users, practitioners and their referring primary care provider; 2) time and flexibility for service users to engage in the quitting process at their own pace; 3) setting progressive goals and building service user confidence; 4) the opportunity to experiment with quit smoking medications; and, 5) the on-going contact with the practitioner/service. Conclusions Service users who are not successful with quitting abruptly may benefit from a CDTS intervention. This study highlights the important role of 'relationships', time and 'flexible' service delivery models in engaging service users who are not initially successful with quitting. The findings of this study have the potential to inform decision-making regarding the value of the CDTS approach for the English Stop Smoking Service and cessation services worldwide.